First description of the male of Anagyrus almoriensis Shafee, Alam & Agarwal (Hymenoptera: Encyrtidae) with details of new host Pseudococcus calceolariae (Maskell) (Hemiptera: Pseudococcidae) on Rubus ellipticus (Rosaceae) from Himalayas - Gupta, Ankita; Zeya, Shahid Bin; Pratt, Corin F.; Joshi, Sunil; Ballal, Chandish R. (Zootaxa, 2022)
The male of Anagyrus almoriensis Shafee, Alam & Agarwal (Hymenoptera: Encyrtidae) is described and illustrated from India along with notes on its associated hosts and types.